2006
DOI: 10.1038/nbt1269
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of antibody cross-reactivity for two subtypes of type A botulinum neurotoxin

Abstract: Broadening antibody specificity without compromising affinity should facilitate detection and neutralization of toxin and viral subtypes. We used yeast display and a co-selection strategy to increase cross-reactivity of a single chain (sc) Fv antibody to botulinum neurotoxin type A (BoNT/A). Starting with a scFv that binds the BoNT/A1 subtype with high affinity (136 pM) and the BoNT/A2 subtype with low affinity (109 nM), we increased its affinity for BoNT/A2 1,250-fold, to 87 pM, while maintaining high-affinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
162
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(167 citation statements)
references
References 46 publications
4
162
1
Order By: Relevance
“…The resulting refinements in existing contacts led to dramatic improvements in kDa and increased buried surface area between E10 and CXCL13, in comparison with the parental clone 3B4. Our findings echo those of Garcia-Rodriguez et al (29), who demonstrated that CDR-based mutations improving the affinity of a BoNT/A1-A2 cross-reactive antibody for the A2 form eliminated an electrostatic clash while also generating a new energetic interaction.…”
Section: Discussionsupporting
confidence: 52%
“…The resulting refinements in existing contacts led to dramatic improvements in kDa and increased buried surface area between E10 and CXCL13, in comparison with the parental clone 3B4. Our findings echo those of Garcia-Rodriguez et al (29), who demonstrated that CDR-based mutations improving the affinity of a BoNT/A1-A2 cross-reactive antibody for the A2 form eliminated an electrostatic clash while also generating a new energetic interaction.…”
Section: Discussionsupporting
confidence: 52%
“…Collected serum were aliquoted and stored at Ϫ80°C before analysis. MSD assays used human MAb ING2 for toxin capture and SULFO-TAG-labeled MAb CR2 as a reporter (13,16). Assay protocols were optimized after screening and comparing eight different MAbs specific for BoNT/A.…”
Section: Methodsmentioning
confidence: 99%
“…Engineering specificity includes reducing the cross-reactivity to other antigens, broadening the specificity to related antigens, and improving the cross-reactivity with nonhuman species [292][293][294][295][296][297][298][299][300][301]. This can be achieved by the same mutagenesis and display technologies used for affinity maturation as phage display technology or computational design approach.…”
Section: Specificity Of Antibodiesmentioning
confidence: 99%